Influence of Dust Aerosols on Snow Cover Over the Tibetan Plateau - Zhao, Dan; Chen, Siyu; Chen, Yu; Gong, Yongqi; Lou, Gaotong; Cheng, Shanling; Bi, Hongru (Frontiers in Environmental Science, 2022)
Dust in the atmosphere and snow on the Tibetan Plateau (TP) remarkably influence the Asian climate, which can influence snow cover by changing radiative forcing. In this study, we investigated the spatial and temporal distributions of dust and snow cover over the TP from 2009 to 2018 and estimated the relative contributions of atmospheric dust and dust-on-snow to the change in snow cover over the northern TP through the use of reanalysis datasets and satellite retrievals. The results show that the high and low centers of aerosol and dust aerosol optical depth (AOD) are roughly similar. Dust concentrations over the TP generally decrease from north to south and from west to east, showing decreasing trends in the winter half-year (December to May). The correlation coefficients between the dust concentration and snow cover over the northern TP are −0.6 in spring. Dust in the atmosphere and on snow over the TP could significantly influence snow cover by changing the radiative forcing, and the influence of dust deposited on snow is greater than that in the atmosphere. Atmospheric dust reduces the surface net solar radiation by −3.84 W m−2 by absorbing shortwave radiation, decreasing the surface temperature by −2.27°C, and finally increasing the snow cover by 1.04%. However, dust deposited on snow can decrease the surface albedo by −0.004 by reducing the surface optical properties, induce surface warming at 0.42°C, and reduce snow cover by −2.00% by rapid snowmelt in the northern TP.